1259. Activity of eravacycline against staphylococci isolated from periprosthetic joint infections. (31st December 2020) - Zhuchenko, Georg; Schmidt-Malan, Suzannah; Patel, Robin; Patel, Robin
Abstract: Background: Perirosthetic joint infections (PJIs) are costly and difficult to treat. The most common causes of PJIs are Staphylococcus aureus and Staphylococcus epidermidis . Eravacycline is a newer tetracycline with promising activity against Gram-positive and negative bacteria which is approved for treatment of complicated intraabdominal infections. Here, the in vitro activity of eravacycline was assessed against bacteria associated with PJI. Methods: 185 staphylococcal isolates, including 38 methicillin-resistant S. aureus (MRSA), 64 methicillin-susceptible S. aureus (MSSA), 62 methicillin-resistant S. epidermidis (MRSE) and 21 methicillin-susceptible S. epidermidis (MSSE) strains were studied. Minimum inhibitory concentrations (MICs) were determined according to Clinical and Laboratory Standards Institute guidelines (range of 0.06-64 µg/ml tested). Results were analyzed using susceptible breakpoints from EUCAST (≤0.25 µg/ml) and the FDA (≤0.06 µg/ml). Minimum biofilm bactericidal concentrations (MBBCs) were determined using a modification of the Calgary biofilm method. Briefly, biofilms were formed on pegged lids in trypticase soy broth, after which the pegged lids were rinsed in phosphate buffered saline (PBS), transferred to a plate containing dilutions of eravacycline in cation-adjusted Mueller Hinton broth (CAMHB) and incubated for 20-24h. Finally, the pegged lids were again rinsed in PBS and transferred to a plate containing CAMHB and incubated for 24h. The MBBC was the lowest concentration with no visible growth. Results: MIC50/90 (range) in µg/ml for MRSA, MSSA, MRSE, and MSSE were 0.125/0.125 (≤0.06-0.25), ≤0.06/0.125 (≤0.06-0.25). 0.125/1 (≤0.06-2), and 0.25/1 (≤0.06-1), respectively. Using the EUCAST susceptible breakpoint, 100% of isolates would be considered susceptible, whereas only 54% would be considered susceptible using the FDA breakpoint. MBBC50/90 (range) in µg/ml for MRSA and MSSA were both 8/16 (4-16); for MRSE and MSSE, the values were 4/16 (2-32) and 8/16 (2-32), respectively. Conclusion: Our data suggest that the FDA susceptible breakpoint may need re-evaluation. Eravacycline has low anti-staphylococcal biofilm activity. Disclosures: Robin Patel, MD, Accelerate Diagnostics (Grant/Research Support)CD Diagnostics (Grant/Research Support)Contrafect (Grant/Research Support)Curetis (Consultant)GenMark Diagnostics (Consultant)Heraeus Medical (Consultant)Hutchison Biofilm Medical Solutions (Grant/Research Support)Merck (Grant/Research Support)Next Gen Diagnostics (Consultant)PathoQuest (Consultant)Qvella (Consultant)Samsung (Other Financial or Material Support, Dr. Patel has a patent on Bordetella pertussis/parapertussis PCR issued, a patent on a device/method for sonication with royalties paid by Samsung to Mayo Clinic, and a patent on an anti-biofilm substance issued.)Selux Dx (Consultant)Shionogi (Grant/Research Support)Specific Technologies (Consultant)